Impact of Gamification Based Formative Assessment Tasks on Higher Order Thinking Skills and Motivation in the Subject of Mathematics Among Primary School Students (Journal of Asian Development Studies, 2025)
Gamification-based formative assessment practices create opportunities for students to engage in an interactive learning environment with prompt corrective feedback, allowing them to monitor their performance. Prior research studies have yet to thoroughly investigate the impact of gamification-based formative assessment on students' higher-order thinking skills and motivation toward mathematics. Therefore, the study intended to cover the gap. True experimental research, utilising a pretest-posttest control and experimental design, was employed to investigate the study. The target population consisted of 248 students from class 5 enrolled in ten government schools in District Astore. A simple random sampling method was used to choose samples from the target population. Data was collected from students using higher-order thinking skills, pretest-posttest, and motivation pretest-posttest scale tools. Experts ensured validity and reliability through pilot testing. The results revealed a substantial difference in the higher-order thinking skills between the experimental group and the control group. Additionally, the Wilcoxon Signed Rank test indicates that the experimental group's motivation level is significantly higher than that of the control group. Hence, it highlights the positive impacts of gamification-based formative assessment tasks on students' motivation and higher-order thinking skills in terms of mathematics teaching. The research results recommended that gamification-based formative assessment practices be integrated into primary mathematics teaching to ensure prompt feedback and monitor performance. It also provides opportunities to improve higher-order thinking skills and motivation, and reduce ethical pressure carried out due to conventional assessment. The study's results can be used to monitor students' performance regularly, providing a unique opportunity to assess the effectiveness of teachers' instructions. Further research studies may be explored with a more extended intervention period on gamification-based formative assessment of higher-order thinking skills and motivation using a mixed-method research design.